Analisis Efisiensi dan Efektivitas Pengelolaan Anggaran Dana Desa Di Desa Tambak Bitin Kabupaten Hulu Sungai Selatan Tahun 2016-2017 - Muthia Nor Fitriani; Saipudin (PPJP ULM, 2019)
This research was conducted (1) for local governments to analyze village fundbudgets' effective value for community empowerment and development. (2) for thecommunity, which is to know good results regarding village economic growth, regional andeffective village fund centers (3) as a reference for further research on the management ofvillage funds for the empowerment and development of rural communities.The scope of this study is to analyze the efficiency and effectiveness of managingvillage budget funds for 2016-2017 in the Tambak Bitin village of Hulu Sungai SelatanRegency. The data analysis technique used in descriptive research is collecting, dividing,exposing, and deciphering data, so the objective results of the problem are obtained from ananalysis of the results of monitoring data. This research also uses quantitative analysis, andthe result is a percentage.The results of this study are that the efficiency of village funds in Tambak Bitin villageis in the inefficient category; this is because village infrastructure is inadequate andpopulation density is high. The level of effectiveness of funds in Tambak Bitin village isincluded in the category of very effective and effective, influenced by the success of thevillage government in regulating village income and prioritizing community needs andservices provided and felt by the community.